Citrus Hystrix D.C Fluid Inhibits the Growth of Escherichia Coli, Pseudomonas aerogenosa, and Bacillus subtilis - Haitami1 , Leka Lutpiatina1 , Akhmad Muhlisin1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Citrus hystrix D.C is a plant traditionally used for herbs and medicinal plants in Indonesia. Citrus hystrix D.C fluid is proven to inhibit the growth of Staphylococcus aureus. The purpose of this study was to determine the ability of the fluid of Citrus hystrix D.C concentrations of 25%, 50%, 75%, and 100% in inhibiting the growth of Escherichia Coli, Pseudomonas aerogenosa, Bacillus subtilis. Material and Method: This research is experimental with Posttest Only Control Group Design. The material used was local Citrus hystrix D.C, fresh and clean green, obtained from the Astambul area, Banjar Regency, South Kalimantan Indonesia. Results: The results showed that there was a zone of inhibition of Citrus hystrix D.C fluid at a concentration of 25%, 50%, 75%, and 100% on the growth of Escherichia Coli, amounting to 7mm, 10mm, 13mm, 15mm. Pseudomonas aerogenosa, amounting to 6mm, 9mm, 13mm, 14mm. Bacillus subtilis, amounting to 6mm, 8mm, 11mm, 14mm. Conclusion: It concluded that the fluid of Citrus hystrix D.C affected the growth of Escherichia Coli, Pseudomonas aerogenosa, Bacillus subtilis with the most significant inhibition zones respectively 15mm, 14mm, and 14mm.